Correlation Compliance Antiretroviral Therapy With Levels Viral Load In HIV Patients At Poly Clinic VCT Abdoel Wahab Sjahranie Samarinda Hospital 2022 - Mukhlis Agus Setiawan Putra; Liniati Geografi; Clara Ritawany Sinaga (UNIVERSITAS SAM RATULANGI, 2023)
ABSTRACT Human Immunodeficiency Virus (HIV) is a virus which can attack and infect human white blood cells and cause a decrease in the human immune system. Antiretrovirals (ARVs) have been shown to prevent HIV transmission because ARVs have a mechanism of action to prevent the gradual replication of the HIV virus. Compliance with taking ARV is very necessary, because non-compliance can cause resistance and make the amount of virus in the blood increase. The success of ARV therapy can be determined by monitoring the levels ofviral load. The objectives of the study were to determine the relationship between the level of compliance with the level ofviral loadat 6 and 12 months on ARV. This type of research is observational analytic with research design cross-sectional. The level of adherence was measured using the MMAS-8 questionnaire and the level ofviral loadtaken from medical record data. The data analysis used was Univariate and Bivariate withChi Square. The study showed that from 60 respondents, the results showed that the category of high compliance was 63.4%, the category of moderate compliance was 13.3% and the category of low adherence was 23.3%. The results of the bivariate test showed that the significance value between the level of patient compliance and the level of viral load 6 months (p= 0.027) and 12 months (p= 0.001) <0.05. There is a significant relationship between adherence to taking antiretroviral drugs with levels of viral load HIV patients at the VCT clinic at the Abdoel Wahab Sjahranie Hospital Samarinda in 2022. Keywords: Compliance with taking medication, Viral Load 6 and 12 months, HIV.